Complementary feeding practices and associated factors ofdietary diversity among uncomplicated severe acutemalnourished children aged 6–23 months in Burkina Faso - Nikièma, Victor; Nadia, Fanou (My University, 2021)
Nutritional treatment of children with uncomplicated severe acute malnutrition(SAM) is based on ready-to-use therapeutic foods (RUTF). With treatment providedat community level, children could have access to other foods, and a reduction in thedose of RUTF could further increase dietary diversity during treatment. We assessedthe dietary diversity score (DDS), the minimum dietary diversity (MDD), the minimummeal frequency (MMF) and the minimum acceptable diet (MAD) of 459 infants andyoung children aged 6–23 months being treated for SAM with different doses ofRUTF. We also investigated the factors associated with DDS. Dietary intake wasestimated using a single 24-h multipass dietary recall, 1 month after startingtreatment, from December 2016 to August 2018. The DDS was calculated on thebasis of eight food groups. Differences between children receiving the reduced RUTFand the standard RUTF dose and factors associated with DDS were assessed byPoisson and logistic regression models. RUTF dose was not associated with DDS(4.07 ± 1.25 for reduced RUTF and 4.01 ± 1.26 for standard RUTF;P=0.77). Foodgroups most consumed by children were grains, roots or tubers (96%) and legumesand nuts (72%). Eggs consumption was low (3%). DDS was positively associated withchild's age, mother's education, household wealth index, urban residence and rainyseason. The present findings show that children with SAM consumed a variety offoods during treatment in addition to the RUTF ration prescribed to them. Reducingthe dose of RUTF during SAM treatment did not impact DDS.
Keywords: associated factors; Burkina Faso; complementary feeding; ready-to-use therapeutic food; severe acute malnutrition